ISLAMIC EDUCATION VALUES IN JAVANESE PROVERBS - Prasetya, Eka; Junanah, Junanah (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2018)
Culture is one of media in spreading Islamic teachings in the Archipelago. In this modern era, however, many people are not familiar with their culture – particularly the values embedded in it including the noble values as contained in Javanese proverbs.  This study aims to explore the noble values inherited by the Javanese ancestors which essentially contain Islamic education values. This is a library research in which the primary sources are 10 Javanese proverbs whose meanings are studied by means of semiotic analysis technique. The results of the research show that Javanese proverbs contain the values of Islamic education in the form of Aqidah (faith), Syariat (rules or regulation), and Akhlak (moral) values. The contextualization of the Javanese culture values in Islamic education can be reflected in three centers of education: in the family, schools and society at large.